The Federal Reserve System Discussed: A Comparative Analysis - M.M.G. Fase; W.F.V. Vanthoor (SUERF - The European Money and Finance Forum, 2000)
In the first half of 2000 the authors of this paper visited the twelve District Reserve Banks in the United States which was followed by a discussion at the Board in Washington. The aim of this visit was to get a deeper insight into the working of the American Federal Reserve System in order to see whether there is a sufficient basis for a comparison with the European System of Central Banks. The direct contacts with many senior and research staff members enabled them to deepen their factual empirical knowledge about the US banking system. The staff set aside a lot of time to discuss the relevant questions and made various members of the Economic Research Departments available for further conversation. Par-ticularly enlightening were the stimulating views of some Reserve Bank presidents on the task and rules of monetary policy.
Keywords: 330; FOMC; Monetary policy; Regional inflation; Specialization; ESCB; Credibility; Transparency; Zentralbank; Vergleich; EU-Staaten; USA